Enhancing Climate Resilience and Productivity in Cambodia Mekong Deltas by Improving Rice-Field Fisheries (Khmer) - Sean, Vichet (WorldFish, 2024)
WorldFish and partners are enhancing RFF systems in Cambodia’s Mekong Delta through study on the rice field pond to enhance the production. CFRs serve as crucial dry-season habitats for fish, ensuring stock regeneration and offering additional benefits to local communities, especially during prolonged dry spells. Efforts also include training farmers in climate-adaptive techniques, promoting better fish stocking, and conserving aquatic habitats. These measures boost productivity and ecological sustainability while building resilience against climate challenges. The initiative underscores the potential of RFF systems to enhance rural livelihoods, strengthen food systems, and support sustainable development in vulnerable regions.